Information about Simulation Software for Testing of Wireless Network - Chaudhari, Kalpana; Karule, P.T (Journal of Information, 2015)
Actual network testing is time consuming and costly for researcher so Solution for this problem is that to test wireless network using open source and free software is available for that .The paper reflects the number of software availability to network model design and its performance . Many authors have worked on various QoS parameters using different service classes in WiMAX. WiMAX is wireless technology for fixed and mobile access and also known by IEEE802.16 standard .Now a day’s WiMAX is fast and suitable wireless technology for urban and rural area which can cover maximum area with minimum infrastructure. IEEE 802.16e-2005 has been developed for mobile wireless communication which is based on OFDM technology and this enables going towards the 4G mobile in the future. In this paper, simulation model based on 802.16e OFDM-PHY baseband (WIMAX) and demonstrated in simulation scenarios with QPSK to find out the best performance of physical layer for WiMAX Mobile. All the necessary conditions were implemented in the simulation according to the 802.16e OFDMA-PHY specification. The study is conducted on various quality parameters impacting the WiMAX service performance of a WiMAX network and also introduces NS3 simulation software to test WiMAX network.